Estatística no ensino médio: uma proposta metodológica baseada na teoria da aprendizagem significativa, utilizando a sustentabilidade como tema contextualizador - Quedi, Rejane Padilha (2024)
Statistics plays an important role in contemporary society and has proven to be an excellent tool for developing essential skills for decision-making in the modern world. However, the problem highlighted by the research professor refers to the fact that students who enter higher education have conceptual gaps, which results in a high failure rate in Statistics subjects. In this sense, the need to develop contextualized teaching strategies and methodologies that are mainly aligned with the National Common Curricular Base (BNCC) became evident, aiming to help teachers promote meaningful learning for Basic Education students. In view of the above, this study is based on the guiding question: How does a contextualized teaching material with the theme of sustainability and supported by the Theory of Meaningful Learning, which is composed of three didactic sequences and a short online course, strengthen the pedagogical practices of Basic Education Mathematics teachers in approaching basic Statistics content? The main objective of this research is to develop teaching materials for high school mathematics teachers regarding the preparation of tables and the establishment of the difference between serial and grouped data and the concepts of population, sample, data collection, arithmetic mean, mode, median, mean and standard deviation for serial and grouped data, in a meaningful, contextualized way and aligned with the BNCC. Methodologically, the research is classified as qualitative and participatory and the data production instruments were questionnaires, semi-structured interviews and the research teacher's logbook. After the feasibility study, which consisted of the application of three teaching sequences by basic education teachers, it was found that there was a need to provide support to teachers regarding the structure of the teaching sequences and the contextualizing theme. In this sense, an initial version of an online course was developed through Google Classroom®, in which 20 high school mathematics teachers participated. The online course had a workload of 30 hours, divided into three modules, namely: The teaching of Statistics in the BNCC and its importance for sustainable development; The Theory of Meaningful Learning; and Presentation of the three didactic sequences. After the course, two of the teachers were supervised in the implementation of the three didactic sequences in the classroom. Data analysis was carried out through Discursive Textual Analysis and the data produced were analyzed in the categories "a priori: pedagogical - materials and resources, predisposition and intervention and monitoring" and "emergent: teacher training". The results indicated that the educational product developed, in the form of a didactic material, subsidized and strengthened the pedagogical practices of high school Mathematics teachers for the approach of basic Statistics content supported by the Theory of Meaningful Learning and contextualized with the theme of sustainability. This study also resulted in an online course in the Distance Education modality, offered institutionally, free, continuous and set in Moodle. Together with the three didactic sequences, the course refers to the educational product linked to this thesis and is available on the website of the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo and on the Educapes website at the link http://educapes.capes.gov.br/handle/capes/747851.